Derechos de propiedad y sistema normativo en la Argentina del siglo XIX - Zeberio, Blanca (2006)
This paper aim to analyze the role that such a concepts like family, inheritance and property played for developing modern Argentine society. Especially how some principles were broken on, while others have been kept on, as the different legal criteria suggests. Rural Law of 1865, Civil Law of 1869 and juridical debates set the interaction rules among different notion of property rights and also different way for labor hiring, either into market rules or out of them. These kind of relations and their coexistent avoided to expand cattle business in a market way.